A fatal case of rhinocerebral mucormycosis - Kamarudin, Nurul Suhaili; Ibrahim, Rosni; Ahmad, Nur Hanani; Masri, Siti Norbaya (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Rhinocerebral mucormycosis is a potentially fatal and progressive angioinvasive fungal infection. It is classically described in patients with uncontrolled diabetes mellitus and hematological malignancies. This report describes a case of progressive rhinocerebral mucormycosis in a patient with poorly controlled diabetes who was on prolonged prednisolone therapy for autoimmune kidney disease. The patient, who was a female, presented to hospital with headache, orbital pain and nasal bridge swelling. Black eschar on nasal mucosae was present on admission. Later, she was started on intravenous fluconazole for the diagnosis of fungal sinusitis. Subsequently, she developed intra-cerebral haemorrhage complicated with transtentorial herniation. Diagnosis of rhinocerebral mucormycosis was later observed by a laboratory finding and the treatment was changed to intravenous amphotericin B. However, the patient succumbed to her illness on the 6th day of hospitalisation. This report discusses the risk factors associated with rhinocerebral mucormycosis as well as the underlying pathogenesis. This report will also highlight the importance of early diagnosis and appropriate treatment for mucormycosis to improve prognosis in patients.